1998
DOI: 10.1002/(sici)1522-7189(199811/12)6:6<219::aid-nt30>3.3.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structural Changes in the Ileum of Mice Fed on δ‐Endotoxin‐Treated Potatoes and Transgenic Potatoes

Abstract: The present work has been designed to study the effect of feeding on transgenic potatoes, which carry the CryI gene of Bacillus thuringiensis var. kurstaki strain HD1, on the light and electron microscopic structure of the mice ileum, in comparison with feeding on potatoes treated with the 'delta-endotoxin' isolated from the same bacterial strain. The microscopic architecture of the enterocytes of the ileum of both groups of mice revealed certain common features such as the appearance of mitochondria with sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…In none of these studies were effects related to GM-materials reported. On the other hand, adverse effects were reported (but not explained) in independent studies by Pusztai (1998Pusztai ( , 2002, Fares and El-Sayed (1998), Ewen and Pusztai (1999) and Pusztai et al, (1999). It is remarkable that these effects have all been observed after feeding for only 10-14 days.…”
Section: Commentsmentioning
confidence: 91%
“…In none of these studies were effects related to GM-materials reported. On the other hand, adverse effects were reported (but not explained) in independent studies by Pusztai (1998Pusztai ( , 2002, Fares and El-Sayed (1998), Ewen and Pusztai (1999) and Pusztai et al, (1999). It is remarkable that these effects have all been observed after feeding for only 10-14 days.…”
Section: Commentsmentioning
confidence: 91%
“…The gene was transmitted into the plant cells via a shuttle plasmid vector after cloning in E. Coli. Fares and El-Sayed (1998) investigated the effect of feeding transgenic potatoes, which carry the CryI gene of Bacillus thuringiensis var. kurstaki strain HD1, on the light and electron microscopic structure of the mice ileum, in comparison with feeding potatoes treated with the "delta-endotoxin" isolated from the same bacterial strain.…”
Section: Gm Plants Potatoesmentioning
confidence: 99%
“…Out of twenty female rats fed the GM tomato, seven were reported to develop stomach lesions [77]. The form of stomach lesions associated to tomatoes could lead to life-threatening hemorrhage, predominantly in the elderly who use aspirin to preclude blood clots [78]. Further, mice fed potatoes engineered to produce the Bt-toxin developed atypical and damaged cells, as well as proliferative cell growth in the lower part of their small intestine [79].…”
Section: Gm Diet Spectacles Lethal Reactions In the Digestive Tractmentioning
confidence: 99%